Sub‐Nanometer Thick Gold Nanosheets: Sub‐Nanometer Thick Gold Nanosheets as Highly Efficient Catalysts (Adv. Sci. 21/2019). Issue 21 (8th November 2019) - Ye, Sunjie; Brown, Andy P.; Stammers, Ashley C.; Thomson, Neil H.; Wen, Jin; Roach, Lucien; Bushby, Richard J.; Coletta, Patricia Louise; Critchley, Kevin; Connell, Simon D.; Markham, Alexander F.; Brydson, Rik; et al.
Abstract : In article number 1900911, Stephen D. Evans and co‐workers develop an ambient aqueous synthesis for preparing atomically‐thin gold nanosheets (termed gold nanoseaweed, AuNSW, because of its morphology, color and aqueous growth). These AuNSWs represent the first free‐standing 2D gold with a sub‐nanometer thickness (0.47 nm, e.g., two atomic layers thick), and exhibit excellent catalysis performance in the model reaction of 4‐nitrophenol reduction, as well as remarkable peroxidase‐mimicking activity.